1999
DOI: 10.1002/(sici)1521-4141(199901)29:01<11::aid-immu11>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of cytokine expression and leukotriene formation in human basophils by growth factors, chemokines and chemotactic agonists

Abstract: Basophils stimulated with IL-3 plus C5a selectively express IL-4 and IL-13 and continuously produce leukotrienes (LT) for hours. C5a combined with IL-5 or granulocyte-macrophage colony-stimulated factor was, however, much less effective in promoting cytokine expression and a late continuous phase of LTC4 production, possibly due to lower expression levels of their receptor alpha chains. Basophils also express several chemoattractant receptors, including high levels of C5a receptors, macrophage chemotactic prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
69
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(74 citation statements)
references
References 41 publications
3
69
0
Order By: Relevance
“…The results of our and other laboratories have demonstrated the expression of multiple chemokine receptors in basophils (13,16,20), and our previous functional survey demonstrated that CCR3 ligands are mainly responsible for the migratory responses of resting basophils (13). Fig.…”
Section: Basophil Tem By Chemokinesmentioning
confidence: 62%
“…The results of our and other laboratories have demonstrated the expression of multiple chemokine receptors in basophils (13,16,20), and our previous functional survey demonstrated that CCR3 ligands are mainly responsible for the migratory responses of resting basophils (13). Fig.…”
Section: Basophil Tem By Chemokinesmentioning
confidence: 62%
“…Eotaxin/CCL11, a natural antagonist of CCR2, was recently shown to induce signal transduction via the ERK-1/2 pathway (30). Human basophils also express CCR2 (31) and can be activated via CCR2, resulting in shape changes (31) and the release of cytokines and leukotriene C 4 (32).…”
Section: Discussionmentioning
confidence: 99%
“…Besides CCR3, which is believed to mediate principally cell recruitment and chemotaxis (as opposed to degranulation) (16,17,27), basophils also express other CCRs, including CCR1 and CCR2. Although the role of CCR1 is still unclear, CCR2 is strongly linked to histamine release and leukotriene secretion (16,22).…”
Section: Basophil Responses To Chemokinesmentioning
confidence: 99%